Contact with and Perceptions of Campus Police Among College Students at a Small-Town University - Finkeldey, Jessica (Criminal justice review, 2025)
Although research has documented an association between sociodemographic and behavioral factors and contact with local police, it remains unclear whether such relationships exist among college students who experience contact with university police. It is also unknown how such factors relate to students’ perceptions of campus police. Given the contentious nature of law enforcement in the U.S. and the racialized climate in higher education, it is imperative to understand how college students’ interactions with and perceptions of campus police fall in relation to the broader narrative of policing. Analyzing data from a current sample of approximately 400 undergraduate students enrolled at a small, public university in the Northeast United States, this study examines the sociodemographic and behavioral correlates of students’ contact with and perceptions of university police. Results suggest there are minimal differences between students with and without a history of police-initiated contact in terms of sociodemographic background. Nevertheless, despite this distribution of contact with campus police, self-identified sexual minorities, racial and ethnic minorities, as well as politically liberal students were among those to possess more negative views of campus police. We discuss these findings as a potential by-product of the broader rhetoric surrounding police-community relationships and racism in higher education.